2018
DOI: 10.1371/journal.pone.0197285
|View full text |Cite
|
Sign up to set email alerts
|

Effects of visual search training in children with hemianopia

Abstract: BackgroundThis study investigates the effect of a new computer-based visual search training (VST) that was adapted for children with homonymous hemianopia (HH).Methods22 children with HH (median age 11 years, 8 months: 6y6m-19y2m) trained at home for 15 minutes twice/day, 5 days/week, for 6 weeks. To assess performance before training (T1), directly after training (T2) and 6 weeks after the end of training (T3), we measured search times (STs) during on-screen search (with eye tracking), and in a real life sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 52 publications
1
7
0
4
Order By: Relevance
“…She soon found that the more conscious awareness she gave to understanding what she was seeing, the more she became able to interpret her visual responses to the movements on her right. This is in line with studies focusing on increasing the detection and awareness of stimuli within the blind hemifield, which have shown that with repeated stimulation, the incidence of reported awareness also increases [27] and may well relate to the type of increased saccadic amplitudes resulting from more structured training in visual search, recently shown to be effective in extending the functional field of vision in children with hemianopia [28].…”
Section: Discussionsupporting
confidence: 84%
“…She soon found that the more conscious awareness she gave to understanding what she was seeing, the more she became able to interpret her visual responses to the movements on her right. This is in line with studies focusing on increasing the detection and awareness of stimuli within the blind hemifield, which have shown that with repeated stimulation, the incidence of reported awareness also increases [27] and may well relate to the type of increased saccadic amplitudes resulting from more structured training in visual search, recently shown to be effective in extending the functional field of vision in children with hemianopia [28].…”
Section: Discussionsupporting
confidence: 84%
“…It can be assumed that the natural gaze behavior of visually healthy people is already optimal, as it is guided by the stimuli from peripheral vision. This, however, may not be the case for patients with tunnel vision or other conditions that occlude the FoV, as is suggested by previous studies of gaze behavior of people with visual impairments [ 23 , 28 , 30 , 33 ]. Here, no stimuli from the periphery of the FoV exist to draw the gaze toward important focus points in the scene.…”
Section: Introductionmentioning
confidence: 91%
“…8 zeigt, wie bei Geradeausblick die Information von der hemianopen Seite fehlt und wie sie durch Augenbewegungen im gesamten Blickfeld wahrgenommen werden kann. Ein von uns speziell für Kinder mit Hemianopsie entwickeltes Softwareprogramm steht seit Kurzem ebenfalls zur Verfügung [21].…”
Section: Erkrankungen Die Zu Halbseitengesichtsfeldausfällen Führenunclassified